Novel robot arm design and implementation for hot forging press automation. Issue 14 (18th July 2019) - My, Chu A.; Le, Chi Hieu; Packianather, Michael; Bohez, Erik L.J.
Abstract : Manual handling of hot and heavy workpiece in forging press industry increases the process time and causes safety risks to workers. To increase the productivity and optimise the use of manpower, manipulators are needed to be designed for supporting the workers handling the workpiece. Designing robots for such applications is challenging since the robot suffers from a heavy payload at the arm tip, and it operates at a high speed in a large workspace. This research addresses the design and implementation of a novel robot for handling workpiece for a given forging press cell. A novel robotic mechanism is designed with two key features: (i) the addition of parallel links in between serial links and (ii) the use of hydraulic actuators for driving robot's joints. The addition of parallel links and the use of hydraulic cylinders are to increase the structural rigidity. It is also to reduce the number of joint variables and restrict the end-effector moving parallel to the ground surface so that the robot grips and releases the workpiece in a more efficient and simplified manner. The effectiveness of the designed robot mechanism is demonstrated through functional tests, and experimental results are carried out on the implemented robot.